Propuesta de inversión para la modernización del proceso de divulgación de la información de la alcaldía de Neiva. (2021)
The purpose of the preliminary project is to modernize the information processes of the Mayor's Office of Neiva-Huila, exploring the advances in communication systems as an alternative for updating in the area of communications in the public administration of the Mayor's Office of Neiva, The changes that are proposed in this proposal is to move from traditional information (radio, the press, flyers, banners, posters, radio spots,) to communicate to users what the Mayor, his cabinet, and councilors are working on, computerizing The information, these changes are not effectively planned by the administration, preferring to invest in the payment of a social communicator in the communications area, Facebook transmission of the management report, WhatsApp group and social networks. The modernization of information dissemination is based on the decision-making of the Mayor of Neiva, for the acquisition of new technological equipment to inform and communicate to users all activities, events, advertising, programs through the Internet and digital programming. or modern Led Screens are one of the electronic devices with the greatest impact on Digital Signage channels, through these it is possible to display data, information, images, videos, etc. From this perspective, the opportunity is presented to present this investment proposal to modernize the information disclosure process of the Neiva Mayor's Office.